Potensi Agroindustri Aren Genjah di Desa Kandolo Kabupaten Kutai Timur Kalimantan Timur - Roslinda, Emi; Mondina, Resta Rene; Hanindita, Shafira (MAKILA, 2025)
Aren genjah is a superior national palm germplasm with high economic potential. Kandolo Village is the only village in Teluk Pandan District where many residents cultivate aren genjah for their livelihood. This study aims to map the potential of aren genjah, compare the characteristics of aren genjah with other commodities, and arrange recommendations for developing aren genjah agroindustry. This study employs a survey method involving 30 farmers selected through purposive sampling. Data was collected through observation and interviews using a list of questions. Data analysis was carried out in a qualitative descriptive with the SWOT method. Aren genjah cultivation continues to be developed as a raw material for the agroindustry by considering land area and market share. In Kandolo Village, agricultural land is dominated by Aren genjah cultivation rather than other commodities. However, the number of farmers cultivating ganja is tiny, as most prefer plantation crops, vegetables, and fruits. The sustainability of the Aren genjah agroindustry is supported by the high market demand for various derivative products. Therefore, a development strategy is required through innovation and product promotion integrated with the development of tourist attractions and local Small and Medium enterprises (SMEs).